Her every move [large type] - Irvin, Kelly (Center Point Large Print, 2021)
"He's a cop trying to stop a serial bomber. And she'll stop at nothing to clear her own name. When a deadly bomb goes off during a climate change debate, librarian and event coordinator Jackie Santoro becomes the prime suspect. Her motive, according to Detective Avery Wick: to avenge the suicide of her prominent father, who was accused of crimes by a city councilman attending the event. Though Avery has doubts about Jackie's guilt, he can't exonerate her even after an extremist group takes responsibility for the bombing and continues to attack San Antonio's treasured public spaces. As Jackie tries to hold her shattered family together, she has no choice but to proceed with plans for the Catrina Ball, the library system's biggest annual fund-raiser. But she also fears the event provides the perfect opportunity for the bomber to strike again. Despite their mistrust, Jackie and Avery join forces to unmask the truth - before the death toll mounts even higher"--